Synthesis and electrocatalytic properties of manganese dioxide for non-enzymatic hydrogen peroxide sensing. (March 2015) - Chinnasamy, Revathi; Mohan Rao, G.; Rajendra kumar, Ramasamy Thangavelu
Abstract: Manganese dioxide nanoparticles were synthesized by chemical reduction route at different growth temperatures of 40 °C, 80 °C, 100 °C and were characterized using X-ray Diffraction (XRD), Field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), Cyclic Voltammetry (CV) and chronoamperometry (CA) analysis. FESEM results show that on increasing growth temperature the morphology changes from clusters into mixture of rods and flakes. XPS analysis reveals the formation of MnO2 . Then these particles were immobilized on Pt electrode. A platinum (Pt) electrode modified with low dimensional MnO2 was investigated as a chronoamperometric (CA) sensor for hydrogen peroxide sensing (H2 O2 ). The sample prepared at 100 °C shows good electrocatalytic ability for H2 O2 sensing when compared with the samples prepared at 40 °C and 80 °C. At an operating potential of 0.3 V vs. Ag/AgCl catalytic oxidation of the analyte is measured for chronoamperometric (CA) monitoring. The CA signals are linearly proportional to the concentration of H2 O2 . It is also found that the morphology of the nanostructure plays a vital role in the detection of H2 O2 .